The Volunteer Motivation Scale (VMS): Adaptation and Psychometric Properties among a Portuguese Sample of Volunteers - Martins, Cátia (2024)
Using self-determination theory, this study examined the autonomous motivation and regulatory styles of volunteers. The Volunteer Motivation Scale (VMS) is one of the main instruments available to assess these constructs, but it requires validation and adaptation for different contexts. Therefore, the goal of this study was to analyze the psychometric properties of the 12-item VMS in a sample of Portuguese volunteers. The sample consisted of 207 volunteers, mostly women (74.4%), aged from 14 to 81 years, from various areas of volunteering. The measures included self-regulation, basic psychological needs, causality orientation, and autonomy support. Confirmatory factor analysis using the lavaan package in R was performed to test a four-factor model and a two-factor model. The results indicated that the four-factor model had a better fit to the data. The VMS showed good internal consistency, discriminant validity, and convergent validity. The VMS can be viewed as a valuable tool for professionals and a promising avenue for future research on the motivations of volunteers.